Empirical modelling of dust storm path attenuation for 5G mmWave - Mezaal M.T.; Aripin N.B.M.; Othman N.S.; Sallomi A.H. (Elsevier B.V., 2025)
The rapid evolution of communication technologies, particularly the emergence of 5G mm-wave networks, presents unprecedented challenges, particularly in regions prone to dust and sandstorms. These environmental factors can significantly impact 5G signals by attenuating radio waves, leading to signal degradation. This paper investigates the complex interplay between dust storms and 5G mm-wave wireless communication, offering a novel and comprehensive analysis that extends beyond existing models. Our study investigates into the impact of dust storms on 5G mm-wave wireless communication, specifically focusing on signal attenuations under both non-line of sight (NLOS) and line of sight (LOS) conditions. Through the utilize of the NYUSIM channel simulator and exploration of parameters such as dust particle size, storm duration, and environmental factors, we present a detailed numerical results. In the NLOS scenario, path loss measurements record substantial values, highlighting the significant impact of dust storms across different mm-wave frequencies. Conversely, in the LOS scenario, our findings reveal distinct patterns of path loss and shadow fading, shedding light on the complex interaction between dust storms and signal propagation. This research marks a significant advancement in the field, providing a quantitative foundation for addressing dust-induced attenuation in 5G mm-wave communication. By emphasizing novel research methodologies and innovative ideas, our study contributes to a deeper understanding of the challenges posed by dust storms in 5G mm-wave wireless communication systems, paving the way for more effective mitigation strategies and network optimization techniques. ? 2024 The Authors